Enzymatically Polymerized Organic Conductors on Model Lipid Membranes - Priyadarshini, Diana (Langmuir : the ACS journal of surfaces and colloids, 2023)
Seamless integration between biological systems and electrical components is essential for enabling a twinned biochemical-electrical recording and therapy approach to understand and combat neurological disorders. Employing bioelectronic systems made up of conjugated polymers, which have an innate ability to transport both electronic and ionic charges, provides the possibility of such integration. In particular, translating enzymatically polymerized conductive wires, recently demonstrated in plants and simple organism systems, into mammalian models, is of particular interest for the development of next-generation devices that can monitor and modulate neural signals. As a first step toward achieving this goal, enzyme-mediated polymerization of two thiophene-based monomers is demonstrated on a synthetic lipid bilayer supported on a Au surface. Microgravimetric studies of conducting films polymerized in situ provide insights into their interactions with a lipid bilayer model that mimics the cell membrane. Moreover, the resulting electrical and viscoelastic properties of these self-organizing conducting polymers suggest their potential as materials to form the basis for novel approaches to in vivo neural therapeutics